Influence of Foreign Economic Activity on the Economic Growth of Russian Regions - Izotov, Dmitry Aleksandrovich (Economy of Regions, 2018)
А study of the influence of foreign trade on economic growth is one of controversial research issues. The economy of Russia is based on close interactions with foreign markets, which are sources of its growth. Russia has a large number of regional economies, which are disproportionately connected with foreign markets. The regional specificity may correct significantly a contribution of foreign trade interactions to the economic growth of Russia. The existing research of the influence of foreign trade on the economic growth of Russian regions are episodic and outdated. The main purpose of the article is to assess the long-term impact of foreign trade on the economic growth of Russian regions in a decade (2007-2016). The methodology of the research is based on the neoclassical model of economic growth expanded by adding the parameters of the foreign trade interactions estimated by regions in stable and current prices. The hypothesis of a long-term positive impact of exports and imports on the Russian regions’ economic growth for all model specifications was confirmed. The consideration of regional specificity has given a more exact assessment of the cumulative contribution of regions to economic growth if the foreign trade relations are compared with the aggregated models. We have revealed that indicators of foreign trade, in general, made a positive contribution to economic growth, compensating negative impact of other factors. The paper shows the dependence of the dynamics of regional economic growth on the current volatility of export and import. We suppose that the generally positive impact of foreign trade on economic growth is corrected by regions, in which production and consumption are subsidized within the existing budgetary process. The tendency of the positive influence of export on economic growth is underestimated due to the regions delivering their production mostly to the domestic market. The tendency of the positive influence of import on economic growth is underestimated due to the regions where there are no largest logistic centres and no interaction with foreign countries. These estimates can be a confirmation of the need to intensify the policy of trade openness with the purpose of accelerating the Russian regional economy.